COMBINING INQUIRY, LEARNING COMMUNITY AND TOTAL PHYSICAL RESPONSE FOR TEACHING ENGLISH - Barep Sari Nauli (English Education Journal, 2015)
This study aims at finding out if the combination of the Inquiry (IQ), Learning Community (LC), and Total Physical Response (TPM) methods of teaching English will be able to improve the performance of the students’ English language skills. The study focuses on the students’ performance to verbally respond to simple instructions with acceptable actions within the context of the classroom and school environments and to give verbal expression for some simple acts: showing how to do something simple, gesticulating, and giving directions (as stated in KTSP or Kurikulum Tingkat Satuan Pendidikan (School Based Curriculum or SBC) in Depdiknas, 2006). In terms of speaking skills, this study concentrates on the pronunciation and comprehension aspects. To achieve the goal of study, an experimental approach with one-group pre-test and post-test design was used. A number of 20 students out of a 58 student population were selected randomly as the sample for treatment. The results showed that the students’ comprehension and pronunciation improved significantly (from 34 to 60). In conclusion, the combination of IQ, LC and TPR of teaching did improve the ability of students to respond to simple instructions, and to express simple speech for giving simple directions, gesticulating, and showing how to do something simple. The hypothesis (Ha) of this research is then accepted as the combined teaching method generated greater ability in English than previous methods.